Pengaruh Metode Hypnoteaching Terhadap Kemampuan Matematika Siswa Pada Materi Perbandingan Trigonometri - Wisnu Siwi Satiti; Hartina Irodatul Aliyah; Khusnul Khotimah (Universitas KH. A. Wahab Hasbullah, 2018)
This research aims of determining the effects of the hypnoteaching method toward the student mathematical abilities in the trigonometry ratio. The type of this research was quasi experimental with nonequivalent control grup design. The study variables consisted of independent variable was the hypnoteaching method and dependent variable was the mathematic competence student. The population in this research includes all students of X grade in the State Senior High School 10 Jombang the consist of 5 class. The sample in this research was students of class X.MIA-1 as the experimental class and students of class X.MIA-2 as the control class. The data were collected by using pretest and posttest questions in a descriptive format. Statistical analysis used is n-gain with independent sample t-test. The result shows that are the average gain normalized the mathematical ability of the experimental class students with the average gain normalized the mathematical ability of the control class students. It is can be proved by the Sig.calculate (0.000) < α (0.05) and reinforced by the result of calculation tcalculate > ttable (6.162 > 1.995) which means Ha is accepted and Ho rejected. Thust, it can conclude that hypnoteaching method has an effect toward the student mathematical abilities in the trigonometry ratio. Keywords: hypnoteaching; student mathematical abilities